(untitled) (Journal of Health, Population and Nutrition, 2010)
The health system of a country needs to be adjusted to patterns of morbidity and mortality to mitigate the income-erosion consequences of prolonged ill-health and premature death of adults. Population-based data on mortality by cause are a key to modifying the health system. However, these data are scarce, particularly for rural populations in developing countries. The objectives of this study were to determine the burdens of health due to major causes of death obtained from verbal autopsy of adults and the elderly and their healthcare-seeking patterns before death in a welldefined rural population. There were 2,397 deaths-613 were among adults aged 15-59 years and 1,784 among the elderly aged 60+ years-during 2003-2004 in the health and demographic surveillance area in Matlab, a rural area of Bangladesh. Trained interviewers interviewed close relatives of the deceased using a structured verbal-autopsy questionnaire to record signs and symptoms of diseases/ conditions that led to death and medical consultations before death. Two physicians independently assigned the underlying causes of deaths with disagreements resolved by a third physician. The physicians were able to assign a specific cause in 91% of the cases. Rates and proportions were used for estimating the burden of diseases by cause. Of all deaths of adults and the elderly, communicable diseases accounted for 18% and non-communicable diseases for 66%, with the proportion of non-communicable diseases increasing with age. Leading non-communicable diseases were diseases of the circulatory system (35%), neoplasms (11%), diseases of the respiratory system (10%), diseases of the digestive system (6%), and endocrine and metabolic disorders (6%), all of which accounted for 68% of deaths. Injury and other external causes accounted for another 5% of the deaths. During terminal illness, 31% of the adults and 25% of the elderly sought treatment from medical doctors, and 14% of the adults and 4% of the elderly died in healthcare facilities. The findings suggest that the health managers and policy-makers of Bangladesh should recognize the importance of prevention and management of chronic diseases and place it on the health agenda for rural people. Key words: Adult; Causes of death; Elderly; Healthcare-seeking behaviour; Mortality; Rural health; Bangladesh DOI: 10.3329/jhpn.v28i5.6161 J HEALTH POPUL NUTR 2010 Oct;28(5):520-528